2016
DOI: 10.21873/anticanres.11101
|View full text |Cite
|
Sign up to set email alerts
|

Chest Wall Deformity in the Radiation Oncology Clinic

Abstract: Abstract. Background Adjuvant radiation therapy for women with breast cancer is associated with a reduction in local recurrence and, in many patients, a survival benefit (1, 2). As risk of cardiac events is correlated with the mean heart radiation dose (MHD), radiation oncological planning often focuses on techniques to reduce the MHD in women with left-sided breast cancer (3). Individual anatomic variation, including breast size, breast ptosis, tumor bed location, heart position and chest wall shape, all impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
1
8
1
Order By: Relevance
“…increased ADC [8] consistent with our results. On the other hand, in non-responding metastases no ADC increase was observed consistent with a sharp increase in the AUC at fraction 3 ( Supplementary Figure 4).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…increased ADC [8] consistent with our results. On the other hand, in non-responding metastases no ADC increase was observed consistent with a sharp increase in the AUC at fraction 3 ( Supplementary Figure 4).…”
supporting
confidence: 93%
“…In one study 3D-CRT was compared to more advanced RT techniques regarding dose to target and organs at risk (OARs) [7]. Another study evaluated 3D-CRT in ten patients with PE treated with whole breast irradiation (WBI) and compared MHDs to those in a group of breast cancer patients without PE [8].…”
mentioning
confidence: 99%
“…Pectus excavatum is the most common congenital chest wall deformity, with an incidence of 1 in 300–1000 births . In one study, 3.7% of 273 patients who underwent RT to left breast tissue had clinically apparent PE . There is a concern that the administration of RT to breast tissue results in a greater radiation dose to the lungs in patients with PE than in those without this condition because of the concavity of the chest wall in the former, leading to a greater frequency of pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%
“…27 In one study, 3.7% of 273 patients who underwent RT to left breast tissue had clinically apparent PE. 28 There is a concern that the administration of RT to breast tissue results in a greater radiation dose to the lungs in patients with PE than in those without this condition because of the concavity of the chest wall in the former, leading to a greater frequency of pulmonary complications. Several recent studies involving dosimetric analysis of DVHs of RT to breast tissue in patients with PE revealed that IMRT delivers a smaller ipsilateral lung dose than 3D-CRT.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in cardiac dose is particularly important in high-risk patients such as this patient having coexistent chemotherapy-induced cardiomyopathy. Other methods of treatment have been proposed to solve this difficult clinical problem including volume-modulated arc therapy, intensitymodulated radiation, and deep inspiration breath-hold technique resulting in cardiac radiation reduction by anywhere from 30% to 70% [9]. But PE creates another complex scenario with the inward deformity of the chest wall causing compression of the heart, which increases not only the exposure of the heart to chest wall radiation but also exacerbates the underlying decreased cardiac output [10].…”
Section: Discussionmentioning
confidence: 99%